1991
DOI: 10.1111/j.1365-2389.1991.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the fixation and availability of sorbed phosphate in soil using an isotopic exchange method

Abstract: An isotopic exchange method was used to characterize quantitatively the fixation and plant availability of phosphate previously sorbed by soils. In general, the exchangeability of the sorbed phosphate was much higher than its desorbability for both soils and clay minerals. Isotopic exchangeability of the sorbed phosphate increased with sorption saturation during the initial stage (1 5-60% saturation), but the increase was less with increasing saturation from 6&90% for all soils tested. Therefore a sorption sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
1
10
1
1
Order By: Relevance
“…It is interesting that P uptake of plants (see Table 4) was larger than the total extractable P lost during the rice growth for Fe and A1 oxide-P complex. In addition, compared to the previous results (He et al, 1991) the recovery of sorbed P by rice plants was larger than the desorbability in 0.02 M KC1 solution for the complexes except for montmorillonite-P at 50% saturation, and was even larger than the isotopic exchangeability for the goethite-P complex. Apparently, a part of the P sorbed by sesquioxides, though not extractable by those chemical reagents, still remains available to plants, whereas P sorbed by montmorillonite may be unavailable to plants although it is readily desorbed even by anion-exchange resin.…”
Section: Plant-availability Of the Adsorbed Phosphatecontrasting
confidence: 42%
See 3 more Smart Citations
“…It is interesting that P uptake of plants (see Table 4) was larger than the total extractable P lost during the rice growth for Fe and A1 oxide-P complex. In addition, compared to the previous results (He et al, 1991) the recovery of sorbed P by rice plants was larger than the desorbability in 0.02 M KC1 solution for the complexes except for montmorillonite-P at 50% saturation, and was even larger than the isotopic exchangeability for the goethite-P complex. Apparently, a part of the P sorbed by sesquioxides, though not extractable by those chemical reagents, still remains available to plants, whereas P sorbed by montmorillonite may be unavailable to plants although it is readily desorbed even by anion-exchange resin.…”
Section: Plant-availability Of the Adsorbed Phosphatecontrasting
confidence: 42%
“…The samples of minerals have been described previously (He et al, 1991). Briefly, the montmorillonite and kaolinite are natural products.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slope of the linear regression denotes the annual change in P concentration. much greater than olsen P due to the occupation of P sorption sites with added P. Furthermore, studies using radioactive 33 P have shown the changes in labile pools tend to be quicker than others (He et al 1991;Daroubetal.2000).…”
Section: Resultsmentioning
confidence: 99%